(untitled) (Fiep Bulletin - online, 2014)
Flexibility is an important physical quality of the neuromuscular function and is of great importance for Physical Education professionals to create action plans to improve the development of athletes. It helps to refine sports techniques, increases muscle and joint mechanical capacity allowing for a more economical use of energy and can work as a lesion inoculator helping develop efficiency, speed and strength (LIMA & SILVA, 2006). In swimming, there are four styles of competition (butterfly, backstroke, breaststroke and crawl), which may have their performances improved or worsened depending on the level of flexibility of the athletes. To check the level of flexibility in each style, we compared eight swimmers aged 13-20 (mean 17.62 years) and the time of specialized practice between 3-13 years in each of the four styles (mean 8.75 years). To assess flexibility, Flexiteste by Araújo (1987) was used. This test involves 20 positions which allow us to assess flexibility in five different regions (ankle/knee; hip; trunk; wrist/elbow; shoulder). Through the test, we detected the highest flexibility region necessary in each style and made an analysis of the swim movement related to the most flexible region.